Managing Zakat Through the Wakalah Zakat System - Noor Aqilah Mohd Hussin; Nurul’ain Mohd; Mastura Razali; Noraini Saro; Nur Shahidatul Akmar Mahyedin (Universiti Sains Islam Malaysia, 2025)
The Journal of Muamalat and Islamic Finance Research, Volume 22 Issue 2 Page (27–39)